A New Rehabilitation Tool in Fibromyalgia: The Effects of Perceptive Rehabilitation on Pain and Function in a Clinical Randomized Controlled Trial. (13th January 2016) - Paolucci, Teresa; Baldari, Carlo; Di Franco, Manuela; Didona, Dario; Reis, Victor; Vetrano, Mario; Iosa, Marco; Trifoglio, Domenica; Zangrando, Federico; Spadini, Ennio; Saraceni, Vincenzo Maria; Guidetti, Laura
Abstract : Introduction / Objective . Fibromyalgia might benefit from a specific tactile and proprioceptive rehabilitation approach. The aim of this study was to perform a randomized controlled trial to determine the efficacy of perceptual surfaces (PS) and physical exercises with regard to chronic pain and physical function in fibromyalgia compared with a control group. Methods . Data from 54 females (18–60 years old) with a diagnosis of fibromyalgia and scoring >5 on the visual analog scale were divided into 3 groups and analyzed: group treated with perceptual surfaces (PS-group), physical exercises group (PE-group), and control group (CG). The Fibromyalgia Impact Questionnaire (FIQ), Health Assessment Questionnaire (HAQ), and Fibromyalgia Assessment Scale (FAS) were administered at baseline (T0), at the end of the treatment (T1) (after 10 rehabilitation sessions over a 5-week period), and at the 12-week follow-up (T2). Results . The PS-group experienced a statistically significant improvement versus the CG in FAS and HAQ scores. Good efficacy with respect to pain and function in the PE-group compared with the CG in terms of FAS, HAQ, and FIQ scores was observed. The adherence ratio was 86% for the PE-group and CG and 90% for the PS-group. Conclusions . According to the results, the PS are as promising as the physical exercises, since results were similar.